PENGARUH AKUNTABILITAS, TRANSPARANSI DAN PENGAWASAN TERHADAP KINERJA PELAKSANAAN ANGGARAN PADA INSTANSI PEMERINTAH - Aprianti, Eka Ratna; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to examine the influence of accountability, transparency, and oversight to the budgetimplementationperformance. This research is a quantitative research. The population is local apparaturs workunit at the environment of local government of Mojokerto district. The sample collection technique has beencollected by using purposive sampling method. The data collection technique has been done by conducting surveymethod. The data has been done by using primary data in theform of questionnaires which have been issued tothe respondents. The analysis method has been carried out by using multiple linear regressions analysis and theapplication instrument of SPSS (Statistical Product and Services Solutions) 20.0 version. The result of thisresearch shows that the presentation of accountability gives positive influence to the implementationperformance, transparencygives positive influence to the budget implementation performance and oversight givespositive influence to the budget implementationperformance.Keywords: Accountability, transparency, oversight, budget implementation performance.